Ventricular septal defect complicating delayed presentation of acute myocardial infarction during COVID-19 lockdown: a case report. Issue 2 (16th February 2021) - Evans, Matthew C; Steinberg, Daniel H; Rhodes, John F; Tedford, Ryan J
Abstract: Background : Post-myocardial infarction ventricular septal defects (VSDs) have become rare in the reperfusion era but remain associated with very high morbidity and mortality. As patients defer prompt evaluation and management of acute coronary syndromes during the COVID-19 global pandemic, the incidence of these and other post-infarction mechanical complications is expected to increase. Case summary : A 37-year-old gentleman with multiple coronary artery disease risk factors presented with intermittent chest discomfort and 1 week of heart failure symptoms. An echocardiogram demonstrated a large muscular VSD and coronary angiography confirmed the presence of an anterior wall infarction. He was subsequently referred for transcatheter VSD repair and showed rapid clinical improvement in his symptoms. Discussion : Post-infarction VSDs remain associated with a high degree of morbidity and mortality. Surgical repair of acutely ruptured myocardium can be technically challenging, and transcatheter repair has emerged as a safe and effective alternative.